2012
DOI: 10.1103/physreva.85.052117
|View full text |Cite
|
Sign up to set email alerts
|

Importance of level statistics in the decoherence of a central spin due to a spin environment

Abstract: We study the decoherence of a central spin 1/2 due to a closed environment composed of spin-1/2 particles. It is known that a frustrated spin environment, such as a spin glass, is much more efficient for decoherence of the central spin than a similar-size environment without frustration. We construct a Hamiltonian where the degree of frustration is parametrized by a single parameter κ. By use of this model we find that the environment can be classified by two distinct regimes with respect to the strength of le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…This integrability is encoded in (quasi-) local integrals of motion (LIOM's), also referred to as l-bits (for localized) 14,[40][41][42][43][44] . We will see in the remainder of this Letter that the combination of the aforementioned phenomena, i.e., violation of ETH, the change in level statistics, and the emergent integrability will largely influence the decoherence properties of the attached probe spin 26,34 .…”
Section: Modelmentioning
confidence: 97%
See 1 more Smart Citation
“…This integrability is encoded in (quasi-) local integrals of motion (LIOM's), also referred to as l-bits (for localized) 14,[40][41][42][43][44] . We will see in the remainder of this Letter that the combination of the aforementioned phenomena, i.e., violation of ETH, the change in level statistics, and the emergent integrability will largely influence the decoherence properties of the attached probe spin 26,34 .…”
Section: Modelmentioning
confidence: 97%
“…In particular, the roles of soft modes close to second order phase transition 27,33 , or the presence of a non-vanishing order-parameter in the bath have been studied in depth. Moreover, the relation of the level statistics of the bath to the decoherence properties of the single spin is well established 34 . Here, we want to capitalize on these insights in order to use the decoherence of a single spin as a probe for a many-body localized system.…”
Section: Introductionmentioning
confidence: 99%
“…1). Past simulations have shown that a high connectivity spin-glass type of environment is extremely efficient to decohere a system [16,[28][29][30], so we may expect that the one-dimensional ring is one of the most difficult geometries to obtain decoherence in short times.…”
Section: E Model and Methodsmentioning
confidence: 99%
“…These processes have a consequence on each component of the system, and could induce decoherence and relaxation. ( [1,2,3,4,5,6,7,8,9]). In order to explore this problem we consider the interesting example of a multipartite quantum system represented by a spin chain, i.e.…”
Section: Introductionmentioning
confidence: 99%